Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar dan Motivasi Belajar Kimia Siswa - Sulandri, Endang; Burhanuddin, Burhanuddin; Al Idrus, Syarifa Wahidah (Chemistry Education Practice, 2025)
The discovery learning model is a discovery-based learning model that is needed to improve learning outcomes and student learning motivation, especially in chemistry subjects which are synonymous with calculating theories, concepts, laws and facts. This research aims to describe the influence of the Discovery Learning learning model on learning outcomes and chemistry learning motivation for class XI students at SMAN 6 Mataram. This research is quantitative research with a quasi-experimental method (Quasi Experimental Design). The results of the research show that there is an influence of the Discovery Learning learning model on student learning outcomes in chemistry subjects. This can be seen from the results of hypothesis testing with the t-test at a significance level of 5%. The calculated significance was lower than 0.05, namely 0.008 < 0.05. In learning motivation, there is also an influence of the Discovery Learning learning model on students' learning motivation in chemistry subjects, which can be seen from the results of hypothesis testing with a t-test with a significance level of 5%. The calculated significance was lower than 0.05, namely 0.01 < 0.05.